Ionic transport in (nano)composites for fuel cells. (18th May 2016) - Rondão, A.I.B.; Martins, N.C.T.; Patrício, S.G.; Marques, F.M.B.
Abstract: Several composite materials were produced using ceria nanoparticles (<25 nm) and LiAlO2 (particle size >1 μm). The oxides were combined with a mixture of Na2 CO3 and Li2 CO3 (eutectic composition), and fired at temperatures in the 600–700 °C range (vacuum assisted in a few cases). The composites were characterized by scanning electron microscopy, X-ray diffraction and impedance spectroscopy, in air, in the 300–600 °C range. Irrespective of composition or grain size all samples exhibited the same type of conductivity dependence on temperature, with a steep change close to the carbonates eutectic temperature. At T > 500 °C all materials have identical conductivity, indicating that molten carbonates dominate the electrical performance. However, at low temperature (300–450 °C) significant differences can be noticed in all composites, with the best performance observed for ceria based composites with larger grain size (close to 135 nm). Graphical abstract: Highlights: High densification (97%) of nanocomposites prepared using vacuum assisted firing at 700 °C. Composite effects at T < 500 °C in ceria-based nanocomposites due to interfacial conduction. High temperature conductivity (T > 500 °C) insensitive to composition and grain size effects. Performance of ceria-based composites matching or even exceeding LiAlO2 -based counterparts.